2012
DOI: 10.1155/2012/647165
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution through Graded-Index Microoptics

Abstract: By solving Helmholtz equations, relationships to describe propagating modes in an arbitrary graded-index planar waveguide are derived. We show that in the quadratic-and secant-index waveguides a minimal mode width is 0.4λ/n, where λ is the wavelength in free space and n is the refractive index on the fiber axis. By modeling in FullWAVE, we show that the high-resolution imaging can be achieved with half-pitch graded-index Mikaelian microlenses (ML) and Maxwell's "fisheye" lenses. It is shown that using a 2D ML,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…The transfer matrix corresponding to the    ŝech -type profiles is easily computed by substituting in eq. ( A2)-(A3) the expressions for   waveguide [57]. The LC described in eq.…”
Section: One Single Profidt With Seed-potentialmentioning
confidence: 99%
“…The transfer matrix corresponding to the    ŝech -type profiles is easily computed by substituting in eq. ( A2)-(A3) the expressions for   waveguide [57]. The LC described in eq.…”
Section: One Single Profidt With Seed-potentialmentioning
confidence: 99%
“…Note, however, that while not making much of the effect, the authors just noticed that with a golden nanostrip applied on the surface, the normally incident light did not penetrate into InP. The energy backflow was also numerically shown to occur [10] when focusing light on the output end of a graded-index microlens. As a mechanism behind the energy backflow, the propagation of a surface wave along the microlens end, alternately leaving and entering the medium, was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The effect also occurs in the focus of linearly and circularly polarized nonparaxial vector beams [22], in various vector modal beams (e.g. Bessel [15,16] and non-paraxial Airy beams [24], X-waves [6]), as well as when the focus is on the medium interface [10] or close to nanostructured surfaces [9,13]. It is worth noting that for paraxial unbounded light fields, the longitudinal component of the Poynting vector is proportional to the intensity and changes no sign [8,26], meaning that for such fields the energy backflow cannot occur in free space.…”
mentioning
confidence: 99%
“…In this work, we combine the advantages of using a several-dozen nanometers wide slit for light confinement [4] and a gradient lens for the sharp focusing of light [10]. The finite-difference time-domain (FDTD) simulation has shown that a planar binary microlens in silicon with a 50 nm wide slit can generate a near-surface focal spot of size FWHM λ∕23 with a 44% energy efficiency.…”
mentioning
confidence: 99%
“…Figure 1 depicts a scheme of a planar graded-index slit lens. We consider a hyperbolic secant (HS) lens whose refractive index depends on the transverse coordinate x as follows [10]: nx n 0 ch −1 πx∕2H, where n 0 is the refractive index on the axis and H is the lens length.…”
mentioning
confidence: 99%